The usage of social media in marketing communication of Croatian institutions of higher education - Jadrić, Ivana, ekonomistica (Array, 2018)
The importance and frequency of social media in marketing communication is undeniable today, especially when the target of such communication are young people (and the puropse is advertising and overall improvement of internal communication). Social media are the main source of information for youth as well as virtual space where they can express and present themselves in the best possible way. The significant role of using social media in everyday communication has been recognized by institutions of higher education and they have become an essential part of their marketing mix. Ultimately, the students are the ones who have the main role in acquiring new communication technologies and their communication networks have tendency to be dense and layered (Quan-Haase, 2007). That is the reason why new technologies like social media are mostly accepted and used by high school and university students. In this paper authors analyse the meaning, influence and usage of social media in the context of institutions of higher education and present the findings of an online survey conducted among teachers in such institutions in Croatia. By analysing the results, authors got 104 replies who helped them to get an insight into activities of institutions of higher education on social media as well as the usage of certain social media by private institutions compared with the public ones. This research confirmed that private institutions of higher education are on the overall more active in the usage of social media. However, Chi-squared test showed almost no difference in usage of the most popular social media Facebook and Instagram in private and public institutions of higher education, whereas there is a difference in usage of other social media. In this research, the intensity of certain social media usage in general in Croatia was also compared with the level of their usage in institutions of higher education.